Changes in superoxide dismutase activity postpartum from Laoshan goat milk and factors influencing its stability during processing. Issue 4 (2nd October 2018) - Li, Yu; Chen, Di; Li, Jing; Zhang, Xue-Xi; Wang, Cun-Fang; Wang, Jian-Min
Abstract: The aim of the study was to evaluate superoxide dismutase (SOD) activity from partum to 165 days postpartum of Laoshan dairy goat milk and factors affecting the stability of SOD by the autoxidation of pyrogallol method. The results indicated that the SOD activity in colostrum milk was significantly higher than that in mature milk; and it first decreased and then increased for mature milk. There was a significant decline in SOD activity from 98.54 U/mL at 65 °C for 30 min treatment to 39.04 U/mL at 100 °C for 5 min treatment. It indicated that SOD activity was not entirely lost, and SOD had strong resistance to high temperature. Maximal SOD activity was recorded at pH 6.5 whereas pH greater or lesser than this resulted in decreased activity. In addition, the change of SOD activity under alkaline conditions was less than that under acidic conditions. SOD activities were 105.12 and 67.08 U/mL when the rotational speeds were 45 and 400 g, respectively. Thus, SOD activity decreased as rotational speed increased. The SOD activity increased when the calcium ion concentration was increased, which ranged from 0.2 to 0.6 mg/mL. SOD activity was significantly increased by 26% in the first 4 days and decreased after 4 days in the process of fermentation. And the activity of SOD for the fifth day decreased 20% over that of the fourth day. These data comprehensively demonstrate a range of conditions change that significantly affects the integrity, activity and function of SOD in goat milk.